Present Values Playing the Role of Efficiency Prices in the One-Good Growth Model - Cass, D.; Yaari, M. E. (Review of Economic Studies, 1971)
Journal Article Present Values Playing the Role of Efficiency Prices in the One-Good Growth Model Get access D. Cass, D. Cass Carnegie-Mellon University Search for other works by this author on: Oxford Academic Google Scholar M. E. Yaari M. E. Yaari Hebrew University, Jerusalem Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 38, Issue 3, July 1971, Pages 331–339, https://doi.org/10.2307/2296386 Published: 01 July 1971